Aplicativo de apoio na conscientização e prevenção do Câncer infantojuvenil - Manica, Pedro Marcelo Roso (2024)
The article discusses the development of an application aimed at raising awareness and promoting the early diagnosis of pediatric cancer. In Brazil, cancer is one of the leading causes of death among children and adolescents. The Pediatric Oncology Center at Hospital São Vicente de Paulo, recognized for its patient care, identified the need for this technological tool. The application uses an algorithm to analyze symptoms and risk groups, facilitating the early identification of possible cancer cases and recommending the pursuit of medical advice. This significantly contributes to improving the rates of cancer detection and treatment.